Indonesia Economic Quarterly, March 2010 : Building Momentum - World Bank (World Bank, Washington, DC, 2018)
The Indonesian Economic Quarterly reports on and synthesizes the past three months’ key developments in Indonesia’s economy. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy for the outlook for Indonesia’s economic and social welfare. Its coverage ranges from the macroeconomy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia’s evolving economy.